Interpretation of Entropy Calculations in Energy Conversion Systems - Haseli, Yousef (Energies (Basel), 2021)
Often, second law-based studies present merely entropy calculations without demonstrating how and whether such calculations may be beneficial. Entropy generation is commonly viewed as lost work or sometimes a source of thermodynamic losses. Recent literature reveals that minimizing the irreversibility of a heat engine may correspond to maximizing thermal efficiency subject to certain design constraints. The objective of this article is to show how entropy calculations need to be interpreted in thermal processes, specifically, where heat-to-work conversion is not a primary goal. We will study four exemplary energy conversion processes: (1) a biomass torrefaction process where torrefied solid fuel is produced by first drying and then torrefying raw feedstock, (2) a cryogenic air separation system that splits ambient air into oxygen and nitrogen while consuming electrical energy, (3) a cogeneration process whose desirable outcome is to produce both electrical and thermal energy, and (4) a thermochemical hydrogen production system. These systems are thermodynamically analyzed by applying the first and second laws. In each case, the relation between the total entropy production and the performance indicator is examined, and the conditions at which minimization of irreversibility leads to improved performance are identified. The discussion and analyses presented here are expected to provide clear guidelines on the correct application of entropy-based analyses and accurate interpretation of entropy calculations.